Steroid-unresponsive Immune-mediated Hepatitis Induced by Durvalumab: : A Case Report - Sajdeya, Omar (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.